CONTRIBUTION OF LEADERSHIP STYLE AND WORK MOTIVATION TOWARD TEACHER PERFORMANCE IN SENIOR HIGH SCHOOLS OF THE STATE KOTO TANGAH PADANG CITY - ernita ernita (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aimed to obtain information about: School head leadership style, motivation of teachers, teacher performance, and the contribution of principal leadership style to teacher performance, the magnitude of the contribution of teachers' work motivation on performance and the huge contribution of leadership style and motivation to work together the performance of teachers in SMAN Tangah Koto Padang District. The population was teachers SMAN Tangah Koto Padang District, comprise of 196 people. Samples were taken with Propotional Stratified Random Sampling technique, comprise of 66 people. Research Intstrument is a questionnaire Likert scale models that have been tested for validity and reliability. The data Analysis was using correlation and simple and multiple regression techniques through the help of SPSS version 12.0. The results showed that: (a) The style of leadership of Senior High School District Tangah Koto Padang generally quite good in carrying out its duties, (b) work motivation of teachers in general have also been good, (c) Teachers Performance in general is also good, (d) Principal's leadership style contributed significantly to the performance of teachers., (e) Work motivation contribute significantly to the performance of teachers and (f) The style of leadership and motivation collectively contribute significantly to teacher performance.